Designing the education model from the educational system of the Command University and the Headquarters of the Islamic Republic of Iran Army - Saeid Seyedi; Ali Mahdavi; mohamad reza sarmadi; Bahman Zandi (علوم و فنون نظامی)
Objective: Designing a model of education from the educational system of the Command University and the Headquarters of the Islamic Republic of Iran Army, In order to provide electronic learning environments for graduate students This university is based on a qualitative approach.Methodology: This research aims to It is practical and in terms of its nature, it is a survey type description. The statistical community of this research, professors Dafos Aja, There are experts and specialists in remote education. To collect data in addition to reviewing texts and documents A semi-structured interview was used. To calculate the dimensions and components using the content analysis method Interviews have been conducted with 20 professors of this university, distance education experts and specialists in the form of targeted sampling. These components have been compiled in the form of distance education model of the Dafos Aja educational system. In order to analyze the information collected from the interview data, the coding method derived from content analysis has been used. In order to analyze the data, the logic of qualitative analysis and categorization of information from Max Kyoda software was used.Findings: It showed that the remote education model of Dafos Aja educational system consists of 10 main components, 26 sub-components and 165 sub-branches.Originality: Each of these components includes specific items that can be used as a basis for action in the distance education system of this university.